Relationship between screen-play scenarios' effectiveness and player classification in elite wheelchair basketball based on match results of Tokyo 2020 Paralympic Games - Taku Yasuda; Kaori Tachibana; Hirotaka Mutsuzaki (Frontiers Media S.A., 2024)
BackgroundThe competitiveness of wheelchair basketball has increased over time. However, screen-play, considered a vital offensive tactic in running basketball, is still poorly clarified. Therefore, this study aimed to clarify the impact of screen-play on scoring and game results in wheelchair basketball and assess the roles of each player classification (PC).MethodsInformation regarding screen-play, including 13 categories such as shot success, location, and PC, was recorded for 22 wheelchair basketball games in the Tokyo 2020 Paralympic Games. This information was analyzed using the chi-square test to evaluate the significant differences in the appearance frequency of variables in each category (categorical variable) between the winning and losing teams and the shot-success rate.ResultsExcept for PC-related categorical variables, comparing the appearance frequency of the winning and losing teams confirmed a significant difference for screen and pass locations (all p < 0.05). Regarding the shot-success rates of the winning and losing teams, a significant difference in five categories was confirmed, including shot and pass locations (all p < 0.05). Regarding the PC, comparing the appearance frequency of the winning and losing teams confirmed a significant difference for PC of the screener (p < 0.05). Significant differences were found in the shot-success rates of the winning and losing teams in nine, five, three, and four categories regarding the PCs of the shooter, user, screener, and passer, respectively, such as shot location, pass location, and type of screen (p < 0.05, respectively).ConclusionIn wheelchair basketball offenses, it may be effective to consider the following points in the scenario lead-up to a shot: Using two different spaces, in the paint and the 3-point field goal area, could be crucial in screen-play. Improving the accuracy of on-the-ball screen plays appears vital, and using off-the-ball screens could also contribute to winning. Allocating approximately 50% of screeners to the middle-point classification (Middle) players and the rest to the low-point (Low) and high-point (High) classification players, at approximately 25% each, may be practical. Regarding winning team player roles, using High shooters and users; Low, Middle, and High screeners; and Middle and High passers contributed to play success.